The 1907 strike: A reassessment - Shear, Keith (My University, 1994)
The 1907 white miners' strike on the Witwatersrand has often been used to illustrate significant trends and changes in the political economy of early twentieth-century South Africa. The principal themes are well-known. First, the maintenance of production during the strike by African and Chinese workers demonstrated that some of the skills of immigrant white miners could be dispensed with, marking the beginning of a long struggle to remove white underground workers from productive to mainly supervisory roles. Second, a significant number of Afrikaners, introduced as strike-breakers, entered the mining industry for the first time. This provided one element in a convergence of interests between the industry and the new Het Volk government, which, anxious to assist the Afrikaner unemployed who constituted both a social threat and a section of its electoral support, requested Imperial troops in support of its ‘right to work’ policy during the strike. This indication of good faith in helping mining capital to reduce working costs through an attack on white labour was also a signal to potential foreign investors and lenders that the Transvaal was ‘safe for capital’; its government had accepted the idea that in fostering the industry it was promoting the state's major source of revenue and financial security, a goal to which any competing social concern would henceforth be subordinated. Despite being used to illuminate such important issues, no detailed account of the 1907 strike has been published, while the few books and articles that offer more than a bare outline of the chief events before commenting on their significance are not always accurate. From this first major conflict between capital and organized labour on the Rand a good deal more can be learned than the bald summary of its outcome conventionally rendered in statistics demonstrating reductions in working costs or an increase in the percentage of locally-born whites employed. Such figures, while doubtless important, contribute little towards an understanding of how these results were achieved, and can be misleading if used to support far tidier metanarratives about relations between state and capital than a detailed discussion of the progress and resolution of the conflict would suggest. The purpose of this paper is to offer a careful reconstruction of the strike that will situate the course of events in the context of the production imperatives of the mining industry; that will shed light on the coercive capacity of the post-reconstruction state; that will illuminate the texture of white workers' experience; that will permit a reading of the significance of the strike against the background of the political history of the period; and that will above all convey something of the magnitude of a conflict that has tended to be diminished by being seen as the first and smallest of a series of increasingly menacing challenges by white labour to the power of state and capital in early twentieth-century South Africa.
African Studies Seminar series. Paper presented 22 August 1994
Keywords: Strikes and lockouts. Gold mining. South Africa. Witwatersrand; Gold miners. South Africa. Witwatersrand; South Africa. Politics and government, 1836-1909